PELATIHAN-A LEBIH BAIK DARIPADA PELATIHAN-B DALAM MENINGKATKAN KECEPATAN PUKULAN LURUS KIRI-KANAN PADA SISWA SMKN-5 DENPASAR - I Gusti Made Adi Swandana; I Nengah Sandi (Sport and Fitness Journal, 2013)
A research to increase the speed of the left-right straight punch with the two types of training ie training hit 25 times faster and 25 times slower eight reps (training-A) and the training to hit 50 times faster and 50 times slower four reps (training-B) was conducted a six-week training in Denpasar Hall of SMK-5 starting at 16:00 until 17:30 pm. Samples of each group of nine people picked at random simple from the students SMKN Denpasar. Each group is given different treatment groups are given training-1-A and group-2-B are given training. Data speed of punches taken before and after training. Data were tested by paired t-test to determine the difference between the mean velocity blows before and after training in each group and unpaired t-test to determine the average velocity difference between the two groups of stroke. Limit of significance used was 0.05 (p <0.05). Different rates of speed blows before and after training in group-1 is 60.22 X / mt, which showed a significant difference p = 0.000 and in group-2 is p = 47.22 X / mt, which also showed a significant difference in the p = 0.000. Punch speed after training between groups showed a significant difference, namely p = 0.000. So that the training-A and-B training can increase the speed of a punch. Training-A better than training-B in increasing the speed of the left-right straight punch. For it is expected that the trainers who train speed left-right straight punch to apply the training to hit 25 times faster and 25 times slower three sets of eight reps in training.